Synthesis and evaluation of silver nanoparticles using Cymodocea rotundata against clinical pathogens and human osteosarcoma cell line - Jayanthi Abraham, Shantanu Saraf, Vakas Mustafa, Yugal Chaudhary, Silambarasan Sivanangam (Journal of Applied Pharmaceutical Science, 2017)
Objective: To evaluate the silver nanoparticles (AgNPs) synthesis by aqueous extract of Cymodocea rotundata against clinical pathogens and human osteosarcoma cell line. Methods: In the present study, AgNPs were synthesized by Cymodocea rotundata by reducing 1 mM silver nitrate (AgNO3) solution. The green synthesized AgNPs were characterized by UV-vis spectroscopy, Atomic force microscopy (AFM), Scanning electron microscopy (SEM), Fourier infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Results: FTIR spectroscopy confirmed the presence of protein as the stabilizing agent surrounding the AgNPs. Morphologically, the nanoparticles were found to be spherical with an average particle size distribution of 24.2 nm. The green synthesized AgNPs showed powerful antioxidant properties in in-vitro antioxidant assays and effective in inhibiting human pathogens. The AgNPs also showed potent cytotoxic effect against MG63 cell lines with an IC50 value of 25.31 μg ml-1 which was confirmed by MTT assay. Conclusions: The results support The advantage of using bio-green method for synthesizing AgNPs with antioxidant, antimicrobial and cytotoxic activities are simple and cost effective.
Keywords: Silver nanoparticles, Cymodocea rotundata, FTIR, SEM, MG63 cell line.